كفاءة الاستثمار في القطاع الخيري بالمملكة العربية السعودية: دراسة حالة منطقة مكة المكرمة - أ. د. حسن محمد أحمد محمد مختار; خالد سعيد علي ال ابو رامي الشهراني (White Nile Journal for Studies and Research, 2022)
The study dealt with the efficiency of investment in the charitable sector in the Kingdom of Saudi Arabia according to the viewpoint of the all interesting sectors. The study highlighting the problem of dominating beliefs held by traditional investors on infeasibility of investing with the charitable sector, thus, the main objective of this study is to assess the efficiency of investment in the charitable sector. The study is descriptive and analytical in nature, the case study method was adopted for the purpose of this study, Makkah Elmukaramah District is selected for representing the case of this study. The study based on a pivot hypothesis as that there is a statistical relationship between investment in charitable sector and the efficiency of the charitable sector. The study comes out with many results, the most interesting is there is a statistical relationship between investment in charitable sector and the efficiency of the charitable sector. The study address many of reasonable recommendations, the most important are: encourage private enterprises and individuals to invest with charitable sectors through provision of rewards, increase awareness within sector's dealers on the importance of investment with this sector on commercial bases.